Humorous and Non-Humorous Effects in Sitcoms: a Relevance-Theoretic Perspective - Wieczorek, Magdalena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2020)
Humorous utterances can be divided into those which are created for their own sake (that is, to amuse others), dubbed autotelic humour, and those which communicate truthful and/or untruthful meanings germane to the ongoing conversation, dubbed speaker-meaning-telic humour (Dynel 2018). The present paper carries out a qualitative analysis of humorous units in sitcom discourse with a view to delineating a number of propositional meanings, which can be potentially derived by the TV recipients. Special attention is confined to one of the most powerful tools used to explain humour in various humorous manifestations, i.e. weak implicatures (Sperber and Wilson 1986 [1995]; Wilson and Sperber 2004). It is believed here that pragmatic COMPREHENSION mechanisms proposed within Relevance Theory and the notion of weakly communicated assumptions are two sides of the same coin since these account not only for the viewer’s recovery of a humorous interpretation but also of an array of non-humorous propositional meanings. Moreover, the participatory framework has been employed as an additional parameter to show the difference in the reception of a dialogue by fictional characters and the viewers.